2022
DOI: 10.1161/jaha.122.026430
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Endothelial Microparticles to Obesity and Cardiovascular Disease Risk in Children and Adolescents

Abstract: Background Microparticles and endothelial microparticles (EMPs) are implicated in accelerating cardiovascular disease (CVD); however, data in pediatrics are limited. We examined the relationship of microparticles and EMPs with adiposity and subclinical CVD risk measures in a pediatric population to determine their potential as biomarkers of CVD risk. Methods and Results A cross‐sectional study of youth (n=280; ages 8–20 years) with a range of body mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Thus, blocking the generation and release of EVs was found to reduce blood pressure in hypertensive rats [ 203 ]. Furthermore, an increase in circulatory EC-EV levels has been found in patients with endothelial dysfunction [ 204 ], obstructive sleep apnea [ 205 ], obesity [ 206 , 207 ], renal failure [ 208 ], coronary artery disease [ 209 ], myocardial infarction [ 210 , 211 , 212 ], β-thalassemia [ 213 ], and stroke [ 214 ]. Nevertheless, it is not clear if the increase in their number contributes to these conditions.…”
Section: Biology Of Extracellular Vesiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, blocking the generation and release of EVs was found to reduce blood pressure in hypertensive rats [ 203 ]. Furthermore, an increase in circulatory EC-EV levels has been found in patients with endothelial dysfunction [ 204 ], obstructive sleep apnea [ 205 ], obesity [ 206 , 207 ], renal failure [ 208 ], coronary artery disease [ 209 ], myocardial infarction [ 210 , 211 , 212 ], β-thalassemia [ 213 ], and stroke [ 214 ]. Nevertheless, it is not clear if the increase in their number contributes to these conditions.…”
Section: Biology Of Extracellular Vesiclesmentioning
confidence: 99%
“…Similarly, in patients with inflammatory bowel disease, granulocyte-derived EVs enriched for metalloproteinases and pro-inflammatory cytokines have been shown to increase intestinal permeability [ 230 ]. Other studies have linked EV-mediated inflammation to CVDs [ 206 , 231 , 232 , 233 , 234 ], MS [ 189 , 235 , 236 , 237 ], and more. Autoimmune diseases can stem from EV-presenting self-antigens that auto-activate lymphocytes and trigger immune cells with antigen specificity for EVs’ own parent cells.…”
Section: Biology Of Extracellular Vesiclesmentioning
confidence: 99%
“…Acute‐phase proteins, cytokines (including IL‐6, IL‐1, and tumor necrosis factor‐alpha [TNF‐α]), adhesion molecules (intercellular adhesion molecule [ICAM] and vascular cell adhesion molecule [VCAM]), and endothelial microparticles (EMPs) have been extensively investigated as indicators of endothelial dysfunction. 5 , 6 , 7 Furthermore, interventions targeting endothelial dysfunction, such as traditional medicine, engineered extracellular vesicles (EVs), and molecular techniques, have shown promise in the prevention and mitigation of cardiovascular events and their complications. 8 , 9 , 10 Consequently, there is significant value in the exploration of novel biomarkers and therapeutic approaches for endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“… 14 In one study, rats exposed to tobacco smoke showed changes in blood EV biomarkers that were associated with lung function decline. 15 In another, smokers with preclinical loss of lung function had a higher circulating level of a type of EV called endothelial microparticles, known to be elevated in vascular-related disorders, 16 than did smokers with normal lung function. Both groups had more endothelial microparticles than healthy nonsmokers.…”
mentioning
confidence: 99%